Pilgrimage to Fallen Gods from Olympia: the Cult of Sport Celebrities - Digance, Justine (Australian religion studies review, 2011)
Contemporary Western society has an abundant variety of role models, with celebrities from all walks of life replacing yesteryear's role models of military heroes and political leaders. However, sport has long provided religious and secular role models dating back to the ancient Olympic Games, and today every two years with the celebration of the summer and winter Olympics, more names are added to the Olympic pantheon of heroes. There is already a discrete acknowledged body of literature investigating celebrity sports men and women. This article draws on this literature specifically examining modern secular pilgrimage to sport celebrities, focusing on those who achieve fame and glory on the Olympic victory dais, but also those whose behaviour has led to their expulsion from Olympia. We suggest that because of the Olympic Movement's philosophy of Olympism, it is different from other non-Olympic affiliated sporting organisations, and the price for transgression on and off the playing field can be higher.